Analysis of Different Urban Forms in Istanbul - Burcin Yazgi; Vedia Dokmeci (European Regional Science Association (ERSA), 2006)
Istanbul has a very rich urban structure due to its historical background as being the capital of three empires. Since urban design has a long tradition of emanating from the past, it can be very stimulating to investigate the urban structure of Istanbul in different locations with different locational, historical and socia-economic background. With this respect Istanbul presents a rich urban structure to reweal the relationships among the different urban characteristics for the urban designers. Thus, the purpose of this paper is to investigate building density with respect to population density, road surface ratio, urban block areas, distance to central business district, to the subcenters and to the sea shores in Istanbul. Multiple regression analysis is used as the research method. Building density is taken the dependent variable and the others independent variables of the analysis. According to the results of the analysis, building density of the neighborhoods is a function of distance to central business district, road surface ratio, urban block area and distance to the sea shore. There is no relationship between the building density and distance to subcenters. Thus, the distribution of density has a wide spectrum within the city depending on the changing life styles, income, history and amenities. The results of the study can be useful for urban planners, urban designers, policy makers, and transportation planners. For further research, it is suggested to investigate the relationship between building density and environmental control.
Keywords: 330